Glucose monomycolates based on single synthetic mycolic acids. (September 2015) - Sahb, Mohaned M.; Al Dulayymi, Juma'a R.; Baird, Mark S.
Graphical abstract: Synthetic 6- O -mycolylglucoses such as that shown have been prepared from a range of α-, keto and methoxy-mycolic acids. Highlights: Glucose monomycolates based on synthetic mycobacterial mycolic acids. Glucose monmycolates of a trans -cyclopropane containing keto-mycolic acid. Glucose monomycolates of cis -cyclopropane methoxy-mycolic acids. Glucose monmycolates of cis -cyclopropane α-mycolic acids. Abstract: The preparation of 6- O -mycolylglucoses (GMMs) from single synthetic mycolic acids matching the overall structure of some of the major natural glucose monomycolates of Mycobacterium tuberculosis and other mycobacteria is reported.